A clinicopathological study of salivary gland tumors - Dr Crysle Saldanha; Dr ParasappaYaranal; Dr Krishnaraj Upadhyaya (Tropical Journal of Pathology and Microbiology, 2018)
Background: To evaluate tumors involving major and minor salivary glands, histopathology is an essential diagnostic method and is the gold standard. This study was carried out to know the incidence of salivary gland tumors, their clinical presentation and diverse morphological patterns.Materials and Methods: A prospective cross-sectional descriptive study was carried out over a period of two years in the department of pathology, Yenepoya Medical College hospital, Mangalore.Data regarding patient demographicswas also recorded. All the epithelial salivary gland tumors were classified according toWHO (2005) histological classification.Results: In the present study, a total of 65 cases of salivary gland tumours was found and an age range of 10-79 years was observed. The most common site affected was the parotid gland 47 (72.31%). Among the 48 (73.85%) benign tumors, pleomorphic adenoma 40 (61.54 %) was most commontumor and remaining 17(26.15%) cases were malignant, of which mucoepidermoid carcinoma 8 (12.31%) was frequently observed.Conclusion: This study highlights the usefulness of histopathologicalstudy of salivary gland tumors with various morphological patterns of benign and malignant salivary gland tumors, which are of utmost value in planning the further management of the patient.